Public Relations Marketing Strategy in Building Brand Awareness Using Product Bundling - Marcellinus Dedo Advent Dewata; Lina Sinatra Wijaya (Jurnal Indonesia Sosial Sains, 2024)
Digital media as a marketing platform today results in increased business competition to capture market share. This research aims to analyze whether using PR marketing strategies, specifically bundled products, can increase brand awareness. The study is descriptive qualitative research, utilizing primary data collected through observation and interviews. The sample consists of 20 respondents, including staff, Anak Panah Kopi employees, and public members in Salatiga. The results concluded that the public relations marketing activities by Anak Panah Kopi to increase brand awareness can be seen in the push and pull strategies. Push strategy uses an interpersonal approach to customers by prioritizing good service. While implementing the pull strategy, Anak Panah Kopi innovates products, provides discounts and bundling promos, collaborates with several influencers, and conducts marketing campaigns by displaying exciting content on Instagram social media to market its products.